2021
DOI: 10.1001/jamapsychiatry.2020.4556
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Effectiveness of Nonspecialist-Delivered Interventions for Perinatal Mental Health in High-Income Countries

Abstract: IMPORTANCE Task sharing-or training of nonspecialist providers with no formal training in counseling-is an effective strategy to improve access to evidence-based counseling interventions and has the potential to address the burden of perinatal depression and anxiety.OBJECTIVES To identify the relevant implementation processes (who, what, where, and how) and to assess the effectiveness of counseling interventions delivered by nonspecialist providers for perinatal depression and anxiety in high-income countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 99 publications
(158 reference statements)
1
42
0
Order By: Relevance
“…First, and similar to other process evaluations of intervention contexts ( Saunders et al, 2005 ), the systematic examination of challenges and facilitators are critical to identify in order to achieve optimal implementation ( Evans-Lacko et al, 2010 ). Second, we found no significant differences between study sites or provider type (NSP vs. specialist), highlighting the external validity of the treatment delivery and growing evidence base of NSP-delivered psychological interventions for perinatal depression and anxiety ( Singla et al, 2000 ), respectively.…”
Section: Discussionmentioning
confidence: 79%
“…First, and similar to other process evaluations of intervention contexts ( Saunders et al, 2005 ), the systematic examination of challenges and facilitators are critical to identify in order to achieve optimal implementation ( Evans-Lacko et al, 2010 ). Second, we found no significant differences between study sites or provider type (NSP vs. specialist), highlighting the external validity of the treatment delivery and growing evidence base of NSP-delivered psychological interventions for perinatal depression and anxiety ( Singla et al, 2000 ), respectively.…”
Section: Discussionmentioning
confidence: 79%
“…It has been recently suggested that nonspecialist providers (such as lay counselors, nurses, midwives, and teachers with no formal training in counseling interventions) may represent an effective strategy to improve access to evidence-based counseling interventions, and that integrating nonspecialist providers with evidence-based counseling interventions has the potential to address the significant burden of perinatal depression and anxiety worldwide [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first, for young adults with depression or substance misuse in low-income and middle-income countries, found moderate effectiveness when compared with control interventions [21]. The second, for anxiety and depression in perinatal patients in high-income countries, found nonspecialist providers may be effective in delivering counseling interventions [22]. However, only two online interventions were included.…”
Section: Challenges Of Digital Mental Healthmentioning
confidence: 99%